Deletion of the RNF6 gene in a patient with epileptic encephalopathy – a case report and literature review - Stefan, Michał; Zapolnik, Paweł; Pyrkosz, Antoni (Pediatria Polska - Polish Journal of Paediatrics, 2022)
Epilepsy is one of the most common neurological diseases of developmental ages, and epileptic encephalopathy is one of its most severe forms. The RNF6 gene encodes a protein that is a ubiquitin ligase. It has been associated so far mainly with the development of neoplastic diseases. We present a case of a 3.5-year-old girl with epileptic encephalopathy and deletion 13q. The patient has been suffering from seizures since infancy. Therapy with 3 antiepileptic drugs and the ketogenic diet reduced the frequency of seizures, but they remained at 2–3 per day. Testing with the next-generation sequencing technique – gene panel and whole-exome sequencing – did not show any pathogenic variants in single genes (single nucleotide polymorphism). The array-based comparative genomic hybridization detected a 75 kbp deletion in the 13q12.13 region containing the RNF6 gene. The RNF6 protein is involved in the development of axonal projections, which suggests that the presumable deletion may affect the presented patient’s clinical features.